ChemInform Abstract: Light‐Driven Nitrile Imine‐Mediated Tetrazole—Ene Cycloaddition as a Versatile Platform for Fullerene Conjugation. Issue 40 (October 2015) - Sugawara, Yuuki; Jasinski, Nils; Kaupp, Michael; Welle, Alexander; Zydziak, Nicolas; Blasco, Eva; Barner‐Kowollik, Christopher
Abstract An efficient methodology for modular fullerene functionalization via photo‐induced nitrile imine‐mediated tetrazole—ene cycloaddition (NITEC) is introduced.